PENGARUH PENDEKATAN PEMBELAJARAN KOOPERATIF TWO-STAY TWO-STRAY TERHADAP HASIL BELAJAR IPA MATERI SUMBER DAYA ALAM - Suprihyatin, Warsi (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
This research was aimed to figure out the effect of Two-Stay Two-Stray cooperative learning approach to natural science subject learning achievement on the material of natural resource on the fourth graders of SD Negeri Karangdadap. Learning achievement studied consisted of 3 aspects; cognitive, affective, and psychomotor aspect. The subject of the research was the fourth graders of SD Negeri Karangdadap covered 2 classes, class IVA totaled 23 students and IV B totaled 26 students. This research was conducted by using experimental method, OneÂ fourth grade students as an experimental class and others as a controlled class. This research was started by pre-test, treatment, and post-test, data collecting technique employed was test and no-test. A non-test technique was used to collect affective aspect data by questionnaire and psychomotorÂ aspect by rating scale by using indicator of responsibility attitude. The obtained data were analyzed by Man Whitney test based on the calculation result, obtained cognitive aspect Z < - ZÎ±/2 or -2,213 < -0,01; affective aspect Z < - ZÎ±/2 or -2,282 < -0,01; psychomotorÂ aspect Z < - ZÎ±/2 or -2,395 < -0,01. Based on the above result, it could be concluded that there was an effect on the application of Two-Stay Two-Stray cooperative learning approach to natural science subject learning achievement on the material of natural resource on the fourth graders of SD Negeri Karangdadap on cognitive, affective, and psychomotor aspects.